2007
DOI: 10.12693/aphyspola.112.1203
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Times in Magnetic Nanoparticles System and Memory Effects

Abstract: Some memory effects in nanoparticle systems, similar to those seen in spin glass systems, may have important device applications, by tuning the interaction and the particle size. Recently, this subject provoked a special interest in nano-sciences. In this work we present a study, by simulation of the mode in which the behavior of a magnetic nanoparticle system is influenced by the superposition of the dimensions' distribution, the effective anisotropy constants and the disposal of nanoparticles in the sample, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Consequently, the magnetic moments associated with nanoparticles tend to align ferromagnetically along the long axis, resulting in a slowing down of magnetic relaxation. The slowing down of magnetic relaxation with h d is in qualitative agreement with the work of Osaci et al [49]. The strength of shape anisotropy or ferromagnetic coupling also gets enhanced with h d and ∆.…”
Section: Simulations Resultssupporting
confidence: 90%
“…Consequently, the magnetic moments associated with nanoparticles tend to align ferromagnetically along the long axis, resulting in a slowing down of magnetic relaxation. The slowing down of magnetic relaxation with h d is in qualitative agreement with the work of Osaci et al [49]. The strength of shape anisotropy or ferromagnetic coupling also gets enhanced with h d and ∆.…”
Section: Simulations Resultssupporting
confidence: 90%
“…In the case of a system, having "memory" effects and/or long-range correlations, such as nonthermal noise, may also occur. 23 Tails of distribution curves of delay time follow power law 24 PðlÞ ≈ l −μ ;…”
Section: Resultsmentioning
confidence: 99%
“…The lower relaxation time is also associated with an increase in the concentration of nanoparticles in Fe 3 O 4 -SiO 2 [7]. The decrease in relaxation time in Fe 3 O 4 , after being encapsulated with SiO 2, can also be related to changes in the anisotropic energy value of the nanoparticles, where the anisotropic energy is also related to the blocking temperature [8,14,20,21]. In our previous study, it was reported that the anisotropic energy of the nanoparticles increased when the Fe 3 O 4 samples were encapsulated with SiO 2 .…”
Section: Magnetic Relaxation Time 𝑀(𝑡)mentioning
confidence: 99%